Hubungan Adaptasi Diri dengan Tingkat Stres Mahasiswa Baru Fakultas Ilmu Keperawatan Universitas Islam Sultan Agung Semarang - Afistian Rizki; Betie Febriana; Wahyu Endang Setyowati (Corona: Jurnal Ilmu Kesehatan Umum, Psikolog, Keperawatan dan Kebidanan, 2025)
Students are individuals who have graduated from high school/high school and are currently pursuing higher education at a university. The study period is an important period to look forward to, even though new students often face challenges in the form of academic stress. The transition period from high school to college, busy schedules, new environments, and homesickness are factors that cause stress (Ajeng Febrianti Rahayu et al., 2021). Adaptation is an important skill to help students face these changes. According to Adimiharja (1993), adaptation is the process of a person adapting to the environment and using resources to solve problems. In the first year of college, the ability to adapt is the basis for success in studying for the next few years (Rahmadani & Mukti, 2020). According to Sarafino (2012),stress is the body's response to demands that exceed an individual's capabilities (Hasanah, 2019). How to deal with stress is different for each person, from avoiding the source of stress to solving the problem that causes it. For new students, this stress occurs because of major changes, especially in the learning system (Paramita et al., 2022).